2016
DOI: 10.1111/ajt.13946
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Calcineurin Inhibitor (Tacrolimus) Weaning Randomized Trial in Long-Term Stable Kidney Transplant Recipients

Abstract: Long-term renal transplant outcome is limited by side effects of immunosuppressive drugs, particularly calcineurin inhibitor (CNI). We assumed that some patients selected for a "low immunological risk of rejection" could be eligible and benefit from a CNI weaning strategy. We designed a prospective, randomized, multicenter, double-blind placebo-controlled clinical study (Eudract: 2010-019574-33) to analyze the benefit-risk ratio of tacrolimus weaning on highly selected patients (≥4 years of transplantation, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 30 publications
0
59
0
Order By: Relevance
“…Nevertheless, because immunosuppression has been shown to alter gene expression 41, 42, 52, 53 and particularly circulating B cells 54 , immunosuppression may affect cSoT. Unfortunately, samples before immunosuppression withdrawal are not available notably as TOL are mainly non-compliant and as intentional immunosuppression withdrawal trials have failed 18, 20 . However, several elements argue against that.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, because immunosuppression has been shown to alter gene expression 41, 42, 52, 53 and particularly circulating B cells 54 , immunosuppression may affect cSoT. Unfortunately, samples before immunosuppression withdrawal are not available notably as TOL are mainly non-compliant and as intentional immunosuppression withdrawal trials have failed 18, 20 . However, several elements argue against that.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no parameter has been identified that will safely permit weaning off immunosuppression, even in trials based on a stringent selection of non-sensitized recipients 1820 . Thus, the intentional replication of immunosuppression withdrawal in renal transplantation requires the integration of appropriate clinical parameters and new laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, changes in immunosuppression for individuals are often based upon patient demographics, clinical variables, or physician experience. Two recent studies attempting to withdrawal CNI from carefully selected recipients were both halted prematurely due to high rates of acute rejection and the de novo formation of DSA (8, 10). These experiences highlight the need to develop biomarkers capable of better identifying those individuals in whom immunosuppressive minimization or even withdrawal is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, large multicenter clinical trials focusing on management of de novo anti‐HLA antibodies, such as the Clinical Trials in Organ Transplantation (CTOT)‐02 trial, were unsuccessful in the enrollment of patients in their intervention phases, largely because of concerns about the toxicity of therapies proposed to patients with otherwise stable graft function . However, the widespread practice of reducing immunosuppression, particularly CNIs, in the early 2000s, has now largely fallen of favor: trials of CNI withdrawal, reduction or avoidance produced mixed results, with some reporting high incidences of acute rejection and dnDSA development even in very low‐risk patients . For instance, following fifteen years of follow‐up, a multicenter trial recently reported that a CNI‐free regimen was not associated with a lower incidence of death by malignancy or cardiovascular disease, but led to a worse death‐censored graft survival .…”
Section: Discussionmentioning
confidence: 99%